1990
DOI: 10.1002/art.1780331210
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibody to th ribonucleoprotein (nucleolar 7–2 rna protein particle) in patients with systemic sclerosis

Abstract: We studied sera of 371 consecutive new patients with systemic sclerosis (SSc; scleroderma) who were first evaluated during 1984-1988. All sera were tested for antinuclear antibodies by immunofluorescence staining using HEp-2 cells as substrate. We excluded 219 sera showing dark nucleoli and screened for antibodies to Th in the remaining 152 sera by immunoprecipitation of a 32P-labeled HeLa cell extract. Fifteen (4.0%) of 371 sera were anti-Th+. Anti-Th antibodies were present in 14 (8.4%) of 167 SSc patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
54
0
4

Year Published

1992
1992
2003
2003

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 20 publications
7
54
0
4
Order By: Relevance
“…All sera were diluted 1:40 in 10 mM phosphate buffered saline, pH 7.3, and tested for ACA by indirect immunofluorescence (IIF) performed on HEp-2 substrate (Diasorin, Stillwater, MN). Specimens exhibiting a nucleolar pattern on IIF were evaluated for anti-Th/To by RNA immunoprecipitation as previously described (4). Briefly, a 20-l serum sample was bound overnight at 4°C to 2 mg protein A-Sepharose CL-4B beads (Amersham Biosciences, Piscataway, NJ), washed 3 times with immunoprecipitation buffer (10 mM Tris HCl, pH 8.0, 500 mM NaCl, 0.1% Igepal), and incubated for 2 hours at 4°C with unlabeled extract from ϳ6 ϫ 10 6 rapidly dividing K562 cells.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All sera were diluted 1:40 in 10 mM phosphate buffered saline, pH 7.3, and tested for ACA by indirect immunofluorescence (IIF) performed on HEp-2 substrate (Diasorin, Stillwater, MN). Specimens exhibiting a nucleolar pattern on IIF were evaluated for anti-Th/To by RNA immunoprecipitation as previously described (4). Briefly, a 20-l serum sample was bound overnight at 4°C to 2 mg protein A-Sepharose CL-4B beads (Amersham Biosciences, Piscataway, NJ), washed 3 times with immunoprecipitation buffer (10 mM Tris HCl, pH 8.0, 500 mM NaCl, 0.1% Igepal), and incubated for 2 hours at 4°C with unlabeled extract from ϳ6 ϫ 10 6 rapidly dividing K562 cells.…”
Section: Methodsmentioning
confidence: 99%
“…In 1990, investigators in our group compared 14 anti-Th/To-positive lcSSc patients with a large group of anti-Th/To-negative lcSSc patients and showed that the patients with anti-Th/To antibody more often had puffy fingers, small bowel involvement, hypothyroidism, and poor survival (4). Two limitations of this and other prior reports on anti-Th/To antibody are the small number of patients evaluated and the relatively brief period of patient followup.…”
mentioning
confidence: 99%
“…We performed indirect immunofluorescence tests using commercially prepared slides of monolayer HEp-2 cells (MBL, Nagano, Japan) as substrate (lo), double-immunodiffusion tests using calf thymus extracts as antigen source ( 3 3 , and immunoprecipitation assays using 32P-orthophosphate-labeled (15) (10). Anti-top0 I was considered positive if the serum antibody produced a precipitin line identical to that produced by the reference serum on double immunodiffusion, or if it immunoprecipitated a protein with a molecular weight of -100 kd from "S-methionine-labeled cell extract, inhibited top0 I enzymatic activity in vitro using commercially prepared calf thymus top0 I (Takara, Kyoto, Japan) according to the method of Goto et a1 (37), and reacted with any top0 I fusion protein including B cell epitope(s) on immunoblots, as described elsewhere (35).…”
Section: Methodsmentioning
confidence: 99%
“…A serum sample was obtained from each patient at the time of the first visit. The patients were classified as having diffuse or limited cutaneous involvement, as described previously (9). One hundred ninety-one had diffuse cutaneous SSc, 174 had limited cutaneous SSc, and 51 were not classified.…”
Section: Methodsmentioning
confidence: 99%
“…A complete history, physical examination, and laboratory evaluation were obtained on each patient as previously described (9). The criteria used for organ system involvement were those described previously (9), but with several exceptions.…”
Section: Methodsmentioning
confidence: 99%